0285 Excessive daytime sleepiness with long sleep duration increases myocardial infarction risk. (25th May 2022) - Wang, Heming; Sofer, Tamar; Saxena, Richa; Purcell, Shaun; Huang, Tianyi; Zhu, Xiaofeng; Rutter, Martin; Redline, Susan
Abstract: Introduction: Excessive daytime sleepiness (EDS) affects 10-20% of the population and is associated with cardiovascular diseases (CVD) and mortality. However, EDS is heterogeneous, associated with both short and long sleep duration. It is unclear whether each subtype is related to CVD. Methods: To understand the association of EDS subtypes (stratified by sleep duration) with incident myocardial infarction (MI), we perform multivariable Cox proportional hazards regression on MI using longitudinal medical record data of 471, 991 individuals free of CVD at baseline from the UK Biobank. Baseline EDS and sleep duration were assessed by self-reported questionnaires. Results: After adjusting for multiple social-demographic and behavioral factors, EDS with long sleep (³9 hours) was associated with a 91% increased incidence of MI (HR=1.91, 95% CI 1.34-2.71) compared to healthy sleep pattern (sleeping 6-9 hours without sleepiness), while EDS with normal (6-9 hours) or short sleep (≤6 hours) was not associated with incident MI. Long sleep without sleepiness was associated with a 39% increase in incident MI (HR=1.39, 95% CI 1.14-1.71). The association of EDS with long sleep was not explained by chronotype, insomnia, sleep apnea, depression, hypertension, or type 2 diabetes, but was confounded with self-reported overall health conditions (HR=1.46, 95% CI 1.02-2.08 after adjustment). Conclusion: Our study suggests the previous association evidence of EDS increasing risk of MI may be primarily driven by its long sleep subtype (high "sleep propensity"), but the underlying mechanisms are unclear. Future work is needed to understand whether there are targetable interventions for this novel sleep phenotype that may improve cardiovascular health. Support (If Any): This research has been conducted using the UK Biobank Resource under Application Number 6818. Funding supports: NHLBI R35HL135818 and R01HL153814.